Unique lead adsorption behavior of ions sieves in pellet-like reduced graphene oxide1. Issue 90 (28th October 2015) - Chen, Dejian; Li, Shunxing; Zou, Liling; Zheng, Fengying
<x xml:space="preserve">Abstract</x> A pellet-like reduced graphene oxide has been presented for lead ions removal like behavior of ions sieves in aqueous solution.